Modulating the Electrical and Mechanical Microenvironment to Guide Neuronal Stem Cell Differentiation - Oh, Byeongtaek (Adv Sci (Weinh), 2021)
The application of induced pluripotent stem cells (iPSCs) in disease modeling and regenerative medicine can be limited by the prolonged times required for functional human neuronal differentiation and traditional 2D culture techniques. Here, a conductive graphene scaffold (CGS) to modulate mechanical and electrical signals to promote human iPSC‐derived neurons is presented. The soft CGS with cortex‐like stiffness (≈3 kPa) and electrical stimulation (±800 mV/100 Hz for 1 h) incurs a fivefold improvement in the rate (14d) of generating iPSC‐derived neurons over some traditional protocols, with an increase in mature cellular markers and electrophysiological characteristics. Consistent with other culture conditions, it is found that the pro‐neurogenic effects of mechanical and electrical stimuli rely on RhoA/ROCK signaling and de novo ciliary neurotrophic factor (CNTF) production respectively. Thus, the CGS system creates a combined physical and continuously modifiable, electrical niche to efficiently and quickly generate iPSC‐derived neurons.